Features of the use of jumping exercises for development of speed-power capabilities for the schoolboys of middle classes - Іващенко, О. В.; Цебенко, А. В. (Physical Education Theory and Methodology, 2012)
The question of the use of jumping exercises which rationally balanced after power and volume taking into account the individual features of organism of schoolboys is examined in the article. Their influence is determined on the dynamics of development of speed-power exercises of students of middle school age during a month.